2020
DOI: 10.3389/fpubh.2020.541885
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DeChoker, an Airway Clearance Device (ACD) Used in Adult Choking Emergencies Within the Adult Care Home Sector: A Mixed Methods Case Study

Abstract: Foreign Body Airway Obstruction (FBAO) is a medical emergency that can result in death, particularly if swift, appropriate action is not taken. It can be a frightening experience for all involved. DeChoker, an Airway Clearance Device (ACD), might provide an additional alternative in the management of choking; however, limited evidence around its safety and effectiveness makes adoption controversial.Objectives: An independent evaluation to explore the experiences of health and care professionals who used DeChok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The literature also describes anecdotal evidence of success with both the LifeVac and DeChoker in two case reports 7,8 . Of note, there are a few relevant factors between the two studies that must be considered despite the reported high PNSD efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature also describes anecdotal evidence of success with both the LifeVac and DeChoker in two case reports 7,8 . Of note, there are a few relevant factors between the two studies that must be considered despite the reported high PNSD efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Within the literature found, there are multiple studies and case series, which report data that may find these two devices effective upon initial examination. 4 , 6 , 7 , 8 , 9 , 10 For example, multiple mannequin trials report significant success in dislodgement with LifeVac use. 4 , 6 , 9 , 10 Although these studies represent optimistic outcomes, this data may not be generalizable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first of a multi-phase global evaluation of ACDs that aims to determine their effectiveness and clarify their role (if any) in future choking intervention algorithms [ 15 ]. Prior to this study, most published data were limited to mannequin studies, case reports with few entries, or only focused on a subset of the population [ 8 , 9 , 14 , 21 , 22 ]. This study included all ACD intervention data available, incorporating all ages from all regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…No injury was found due to LifeVac in the cadaver evaluation [ 26 ]. Other studies have limited information on safety [ 8 , 9 , 14 , 21 , 22 ]. Unfortunately, self-reporting has been shown to have poor sensitivity for detecting adverse events [ 24 , 25 ], which is compounded in this study by limited patient follow up and the data quality concerns described previously.…”
Section: Discussionmentioning
confidence: 99%